SHORT VIDEO MARKETING AND GEN Z’S PURCHASE INTENTION: THE ROLE OF BRAND ATTITUDE ON TIKTOK - Andari, Triana Septi; Simbolon, Freddy Pandapotan (Ikatan Dosen Menulis, 2025)
Amid the exponential rise of social media platforms particularly TikTok scholars have acknowledged its dual functionality as both a medium of communication and a potent marketing instrument for engaging contemporary consumers. The platform’s hallmark short-form video format has revolutionized the digital marketing landscape, enabling brands to craft interactive and immersive content that significantly affects consumer behavior. This study focuses on evaluating how short video marketing influences the purchase intentions of Generation Z in DKI Jakarta, with brand attitude serving as an intervening variable. Data was obtained from 100 active TikTok users who had previously made purchasing decisions influenced by short video content. Employing a quantitative methodology, the study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data. The research offers insights into how strategic use of short-form videos can shape consumer attitudes and purchasing behavior. The results demonstrate that variables such as engaging content, scene-based experiences, participatory interactions, perceived usefulness, and celebrity involvement do not exert a significant influence on brand attitude. Conversely, perceived enjoyment emerges as a critical determinant in fostering favorable brand perceptions, underscoring the necessity of producing content that is both enjoyable and captivating. Furthermore, brand attitude exerts a substantial effect on purchase intention, indicating that positive brand perceptions enhance consumers’ likelihood of making purchases. Consequently, marketers are encouraged to prioritize emotional resonance and entertainment value over mere visual appeal, interactivity, or celebrity influence. The study underscores the pivotal role of engaging short video content in cultivating positive brand attitudes and stimulating purchase intentions among Gen Z audiences.